Impact of National Education Policy 2020 on India’s Educational Landscape: A Comprehensive Review - Rizvi, Zakia (AG Volumes, 2025)
Comprehensive, interdisciplinary, and skill-based education are the cornerstones of India’s new "National Education Policy 2020 (NEP 2020)", an ambitious plan to overhaul the country’s educational system. This review study delves deep into NEP 2020, looking at many studies that have looked at how it would affect India’s education system. The policy emphasizes critical thinking, conceptual understanding, and practical application, moving away from rote memorization. It integrates technology, vocational training, and flexible learning pathways to foster an inclusive and globally competitive education system. According to the study’s findings, "NEP 2020" is a big step in improving educational quality by giving students the tools they need to use what they’ve learnt in practical situations. By addressing existing challenges and promoting innovation, the policy holds the potential to modernize India’s education system and align it with international standards, thereby preparing students for future global opportunities.